Exploring Whether White Male Postsecondary Presidents Respond to Racism. Issue 1 (2nd January 2020) - Tevis, Tenisha
ABSTRACT: Most recently, leaders of predominantly White institutions, who are mostly White and male, have been called upon to address the racial violations that have plagued college campuses as well as their surrounding and outer communities. However, these particular leaders have been charged with mishandling racism. Drawing on 2015, which was deemed the year of race, including the incidents that took place at the University of Missouri, the author explored whether White male presidents can respond to racial discord. Utilizing White Fragility, this cross-case analysis offers strategies for these leaders, such as institutional communication and improved hiring practices; yet, the findings also provide insight into the pitfalls that have the potential to maintain status quo and perpetuate privilege.